Global Christianity : contested claims - Wijsen, Frans Jozef Servaas, 1956-; Schreiter, Robert J. (Studies in World Christianity and Interreligious Relations, 2007)
In 2002 Philip Jenkins wrote The Next Christendom . Over the past half century the centre of gravity of the Christian world has moved decisively to the global South, says Jenkins. Within a few decades European and Euro-American Christians will have become a small fragment of world Christianity. By that time Christianity in Europe and North America will to a large extent consist of Southern-derived immigrant communities. Southern churches will fulfil neither the Liberation Dream nor the Conservative Dream of the North, but will seek their own solutions to their particular problems. Jenkins' book evoked strong reactions, a bit to his own surprise, as the book contained little new. In the United States of America, the prospect of a more biblical Christianity caused reactions of alarm in liberal circles. In contrast, conservatives were delighted by the same prospect. In Europe the book landed in the middle of the debate on Europe as an exceptional case. It was detested by those who stick to the theory of ongoing and irreversible secularisation and welcomed by those who see a resurgence of religion, also in Europe. In the present volume, scholars of religion and theologians assess the global trends in World Christianity as described in Philip Jenkins' book. It is the outcome of an international conference on Southern Christianity and its relation to Christianity in the North, held in the Conference Centre of Radboud University Nijmegen, the Netherlands.